End‐to‐End Pierced Carbon Nanosheets with Meso‐Holes - Minjun Kim; Hiroki Nara; Yusuke Asakura; Takashi Hamada; Peng Yan; Jacob Earnshaw; Meng An; Miharu Eguchi; Yusuke Yamauchi (Advanced Science)
Abstract The remarkable properties of 2D nanomaterials are well known. However, their high interfacial adhesion energy often leads to restacking issues, limiting their potential in various applications. A strategic synthetic approach is presented to overcome this challenge. Specifically, the study first demonstrates the use of layered aluminosilicate as a sacrificial 2D template to allow the growth of highly ordered meso‐holey polymeric layers, which can be subsequently exfoliated upon the removal of aluminosilicate and thermally converted to perpendicularly open meso‐holey carbon (POMC). On the other hand, perpendicularly blocked meso‐holey carbon (PBMC) is obtained with non‐sacrificial 2D template of graphene oxide. When both POMC and PBMC are evaluated by operando hydrodynamic electrochemical impedance spectroscopy and transmission line model analysis for electrochemical reduction of oxygen, POMC achieves a remarkable improvement of charge transfer and mass transfer by up to 4.1 and 7.9 times, respectively, as compared to PBMC. This study therefore highlights the importance of perpendicularly open 2D nanoarchitectures in circumventing the restacking effect, offering valuable insights for leveraging 2D nanomaterials with open meso‐holes in various applications.